Neurological Soft Signs, Spontaneous and Treatment Emergent Extrapyramidal Syndromes in Black Africans With First Episode Schizophrenia - Ojagbemi, Akin; Chiliza, Bonga; Bello, Toyin; Asmal, Laila; Esan, Oluyomi; Emsley, Robin; Gureje, Oye (Frontiers in Psychiatry, 2018)
Background: Very little is known about the relationship between spontaneous and treatment-induced motor syndromes in Africans with first episode schizophrenia. Objective: We investigated the association between spontaneous NSS and EPS, with treatment-induced EPS in a homogenous sample of Black Africans with first episode schizophrenia. Methods: We examined Xhosa (South Africa) and Yoruba (Nigeria) patients, using the Neurological Evaluation Scale and extrapyramidal symptoms scale before and at 3 months after exposure to low dose flupenthixol decanoate. Pearson’s correlations and Linear regression models, controlling for duration of untreated psychosis (D.U.P) and premorbid adjustments, were used in examining associations. Results: Among 99 participants in the baseline sample, 91 (91.8%) and 20 (20.2%) had at least one definite NSS and EPS, respectively, before exposure to antipsychotics. Treatment-induced EPS were recorded in 34 (38.6%). Spontaneous EPS was associated with treatment-emergent Akathisia in participants with a longer D.U.P (r=0.75, β=0.70, p=0.008). This association was specific for Parkinsonism (r=0.75, β=0.85, p=0.008) and dyskinesia (r=0.75, β=1.70, p=0.008). Conclusion: Similar to previous findings for tardive dyskinesia in studies implementing longer-term follow-up, spontaneous EPS may also predict short-term antipsychotic-induced EPS such as akathisia. These results may be important for early identification of patients at risk of treatment-induced Akathisia-linked psychomotor agitation in first episode schizophrenia.